Advocating for the rights of women migrant workers The Philippine government's revalida in the 64th session of the UN Committee on the Elimination of Discrimination Against Women (CEDAW). ([Quezon City] Center for Migrant Advocacy; Commission on Human Rights; United Nations Development Programme, 2016)
This publication is a compedium of reports, arguments, and counter arguments that were presented during the UN CEDAW review process in 2015 & 2016, drawing special attention to the rights of women migrant workers.

The Philippine government reported at the 64th session of the Unted Nations Committee on the Elimination of Discrimination Against Women (UN) in July 2016 at Geneva, Switzerland. Migrant rights advocates took this opportunity to raise gender-based discrimination and inequalities experienced by Filipino women migrant workers in the context of accountabilities by state and non-state actors vis a vis the Convention on the Elimination of All Forms of Discrimination Against Women (CEDAW).

With 189 member States of the UN (95%) voluntarily binding themselves to the CEDAW, the CEDAW platform is important in advocating for the rights of all women migrant workers.
Part 1: Revisiting the Legal Framework -- Part 2: The Review Process: Claims by State and Non-State Actors -- Part 3: Concluding Observations and Way Forward
Keywords: Women foreign workers -- Civil rights -- Philippines; Foreign workers, Filipino -- Civil rights; Foreign workers, Filipino -- Government policy; Philippines -- Emigration and immigration -- Government policy